2019
DOI: 10.1177/1934578x19856792
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Studies on Four Indonesian Epiphytic Medicinal Plants: Drynaria rigidula, Hydnophytum formicarum, Usnea misaminensis, and Calymperes schmidtii

Abstract: Phytochemical studies performed on 4 Indonesian epiphytic medicinal plants, Drynaria rigidula L., Hydnophytum formicarum Jack, Usnea misaminensis (Vain) Motyka, and Calymperes schmidtii Broth., revealed 11 known secondary metabolites (1-11), reported from these species for the first time. The methanol extracts and their fractions were screened against infective agents and cancer cells. The dichloromethane fractions of H. formicarum, U. misaminensis, and C. schmidtii showed activity against lung cancer cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The study of Usnea misaminensis which has the potential as anti-inflammatory was confirmed by Nugraha in his journal which stated that the extract contained usnic acid and salizinic acid [2]. This is supported by reports that usnic acid and salicylic acid have antibacterial activity by Cansaran,et al and Candan,et al [8,9].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The study of Usnea misaminensis which has the potential as anti-inflammatory was confirmed by Nugraha in his journal which stated that the extract contained usnic acid and salizinic acid [2]. This is supported by reports that usnic acid and salicylic acid have antibacterial activity by Cansaran,et al and Candan,et al [8,9].…”
Section: Introductionmentioning
confidence: 78%
“…Usnea misaminensis has also been reported to have potential as an anti-acne based on its antioxidant, antibacterial and lipase inhibitory activities by Batubara et al which showed that Usnea misaminensis was able to inhibit the growth of acne [3]. Usnea misaminensis also exerted cytotoxicity against oral KBcancer cells, NCI-H187 lung cancer cells, and MCF-7 breast cancer cells [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous notable study on lichens of Indonesian origin reported the cytotoxicity of the methanol crude extract from Usnea misaminensis against the KB cell, lung cancer cell NCI-H187 and breast cancer cell MCF-7 with IC 50 values of 28, 11, and 30 μg/mL, respectively [ 11 ]. Lecanoric acid, a didepside from Parmelia cetrata was reported to be toxic against Caenorhabditis elegans , causing 80% mortality at a concentration of 100 μg/mL [ 12 ].…”
Section: Introductionmentioning
confidence: 99%